2007
DOI: 10.1038/nature06101
|View full text |Cite
|
Sign up to set email alerts
|

The detection of carbonation by the Drosophila gustatory system

Abstract: There are five known taste modalities in humans: sweet, bitter, sour, salty and umami (the taste of monosodium glutamate). Although the fruitfly Drosophila melanogaster tastes sugars, salts and noxious chemicals, the nature and number of taste modalities in this organism is not clear. Previous studies have identified one taste cell population marked by the gustatory receptor gene Gr5a that detects sugars, and a second population marked by Gr66a that detects bitter compounds. Here we identify a novel taste moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
122
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 22 publications
19
122
1
Order By: Relevance
“…However, when needing to lay eggs, the attraction for AA overrides this positional repulsion, thereby allowing females to deposit their eggs on AA-containing food. Other studies have revealed opposing behavioral responses to a single compound; when detected as carbonation by the gustatory system, CO 2 is attractive (27), but when detected as an odorant, it is aversive (28). However, our experimental setup is unique in that opposing behavioral responses to a single stimulus (AA) are concurrently induced and assayed, affording direct observation of the competition between the 2 behavioral drives.…”
Section: Discussionmentioning
confidence: 99%
“…However, when needing to lay eggs, the attraction for AA overrides this positional repulsion, thereby allowing females to deposit their eggs on AA-containing food. Other studies have revealed opposing behavioral responses to a single compound; when detected as carbonation by the gustatory system, CO 2 is attractive (27), but when detected as an odorant, it is aversive (28). However, our experimental setup is unique in that opposing behavioral responses to a single stimulus (AA) are concurrently induced and assayed, affording direct observation of the competition between the 2 behavioral drives.…”
Section: Discussionmentioning
confidence: 99%
“…Water has earlier been reported to be critically important for attraction to traps baited with synthetic fruit odors (Zhu et al 2003). Drosophila melanogaster sense water with gustatory receptor neurons on the proboscis, projecting into a specific region of the suboesophagal ganglion, and with hygrosensory neurons located on the antennae, projecting into the antennal mechanosensory centre (Fischler et al 2007;Liu et al 2007;Inoshita and Tanimura 2008). It is remarkable that stimuli from outside the antennal lobe, the olfactory center, generate or contribute to an upwind flight response in D. melanogaster.…”
Section: Trapping Study Of Diel Flight Period In the Laboratorymentioning
confidence: 99%
“…Antennal perception of carbon dioxide is interpreted as an alarm signal and generates an avoidance response, 29 whereas the perception of carbon dioxide via taste receptors on the proboscis is interpreted as the presence of a fermenting food source and elicits an attractant response. 30 These observations and behavioral responses to pheromones would suggest that inputs from specialized chemosensory systems are processed via distinct specialized neural pathways. Nevertheless, one cannot exclude that input from olfactory receptors and gustatory receptors might often be integrated, a notion that is supported by covariant transcriptional modules that contain both Gr and Or transcripts.…”
Section: Mechanism Of Plasticity Of Chemoreceptor Expressionmentioning
confidence: 99%